A comparison of visible wavelength reflectance hyperspectral imaging and Acid Black 1 for the detection and identification of blood stained fingerprints. Issue 4 (July 2016) - Cadd, Samuel; Li, Bo; Beveridge, Peter; O′Hare, William T.; Campbell, Andrew; Islam, Meez
Abstract: Bloodstains are often encountered at scenes of violent crime and have significant forensic value for criminal investigations. Blood is one of the most commonly encountered types of biological evidence and is the most commonly observed fingerprint contaminant. Presumptive tests are used to test blood stain and blood stained fingerprints are targeted with chemical enhancement methods, such as acid stains, including Acid Black 1, Acid Violet 17 or Acid Yellow 7. Although these techniques successfully visualise ridge detail, they are destructive, do not confirm the presence of blood and can have a negative impact on DNA sampling. A novel application of visible wavelength hyperspectral imaging (HSI) is used for the non-contact, non-destructive detection and identification of blood stained fingerprints on white tiles both before and after wet chemical enhancement using Acid Black 1. The identification was obtained in a non-contact and non-destructive manner, based on the unique visible absorption spectrum of haemoglobin between 400 and 500 nm. Results from the exploration of the selectivity of the setup to detect blood against ten other non-blood protein contaminants are also presented. A direct comparison of the effectiveness of HSI with chemical enhancement using Acid Black 1 on white tiles is also shown. Highlights: Blood stained fingerprints are commonly encountered at scenes of violent crime. Novel application of visible wavelength reflectance hyperspectral imaging Demonstrated ability to distinguish between blood and other protein contaminants Direct comparison of HSI effectiveness against DSLR and Acid Black 1 enhancement HSI identified blood stained fingerprints before and after chemical enhancement